Substrate for drug solution impregnation
By reasonably configuring the proportions of natural fibers, synthetic fibers and bonded fibers in the paper, the problems of slow production speed and insufficient absorption in the prior art are solved, and efficient chemical liquid absorption and paper strength improvement in the production process are achieved.
Patent Information
- Application Number
- JP2023122485
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-27
- Publication Date
- 2025-02-06
AI Technical Summary
The existing chemical liquid adsorbent materials have problems such as slow production speed, insufficient absorption rate and easy to break during the production process, especially when the chemical liquid impregnation process is prone to paper cutting and machine contamination.
Using single or multi-layer paper, containing 20-80% natural fibers, 20-70% high melting point synthetic fibers and 20-30% bonded fibers, the strength and absorption of the paper are improved by controlling the fiber ratio and density.
It realizes the reduction of paper damage during the chemical liquid impregnation process, improves absorption rate and production efficiency, and ensures the strength and liquid absorption performance of paper.
Smart Images

Figure 2025018616000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a substrate for impregnation with a chemical solution, which is used for impregnating and retaining a volatile chemical and releasing it into the air at room temperature, and more specifically, to a substrate for impregnation with a chemical solution, which has excellent liquid absorption properties for chemical solutions for the purposes of killing insects, sterilizing, controlling insects, repelling pests, providing fragrance, deodorizing, and the like. [Background technology]
[0002] Substrates for impregnating chemical solutions are used in wicking-type liquid air fresheners and deodorants, where the chemical solution in the container is wicked up and replenished into the substrate while the chemical volatilizes from the substrate into the atmosphere, and as indicators to show the effective period of insect repellents, deodorants, etc. The indicator is configured to display a message indicating the end of the effective period as the amount of the chemical solution decreases due to evaporation. When an indicator function is imparted to a chemical solution-impregnated substrate, the chemical solution is not supplied over time, and therefore, in order to achieve the target chemical solution effect and the effective period of the indicator function, various proposals have been made regarding the liquid absorption performance of the chemical solution-impregnated substrate and the imparting of the indicator function.
[0003] Patent Document 1 describes a papermaking method that contains both mercerized pulp and non-mercerized pulp, in which the blending ratio of non-mercerized pulp is 30 to 90 mass %, and the density is 0.30 to 0.38 g / cm 3 , A base paper with an internal bond strength of 50 mJ or more has been proposed. It is explained that the use of mercerized pulp results in a base paper with high bulk, low density, and high chemical impregnation rate. Patent Document 2 describes a chemical-impregnated substrate having a first layer and a third layer mainly made of cellulose fibers and a second layer made of cellulose fibers and synthetic fibers laminated between them, which has a chemical-impregnated substrate surface that has good absorbency and diffusibility when a chemical solution is dropped onto the surface of the chemical-impregnated substrate to impregnate the substrate. The chemical-impregnated substrate has a cellulose fiber / synthetic fiber blending ratio of 20-80:80-20% by weight in the second layer, the cellulose fiber contains at least 50% by weight or more of mercerized pulp or cotton linter pulp, the synthetic fiber is made of main fiber and binder fiber, the main fiber / binder fiber blending ratio is 20-80:80-20% by weight, the first layer, the second layer, and the third layer have a layer ratio of 45-35:30-10:45-35% by weight, and the chemical-impregnated substrate has a basis weight of 75-500 g / m 2 , and density is 0.25~0.50g / cm 3 It has been proposed that However, in terms of productivity in the chemical impregnation process, there is a demand for further improvement in production speed, and the absorption speed of the chemical solution in the substrate proposed by these methods is insufficient. If the density of the substrate is further reduced in order to increase the absorption speed of the chemical solution, the substrate will break during the chemical impregnation process due to insufficient strength of the substrate. There is a demand for a substrate that has the strength required for the production process and has an improved absorption speed of the chemical solution. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-168514 A [Patent Document 2] JP 2015-193954 A Summary of the Invention [Problem to be solved by the invention]
[0005] In the past, the use of mercerized pulp and cotton linters has been proposed for use in chemical-impregnated substrates (hereinafter also referred to as substrates) used in indicators and the like impregnated with chemicals, in the face of demands for improved productivity. However, these proposed substrates are insufficient for the required absorption speed of chemicals, and improvements have been required. In addition, the approach of reducing the density of the substrate to improve chemical impregnation was not a desirable measure because it would lead to deterioration of operability due to the occurrence of paper breaks and machine stains during the papermaking process, and would significantly cause breakage of the substrate during the chemical impregnation process. An object of the present invention is to provide a substrate for chemical solution impregnation that quickly absorbs a chemical solution and is less likely to break during production. [Means for solving the problem]
[0006] 1. It is a single-ply or multi-ply paper, Papermaking fibers include natural and synthetic fibers, The synthetic fiber is contained in an amount of 20% by weight or more and 80% by weight or less based on the total fiber for papermaking, A chemical solution-impregnated substrate comprising a paper layer containing, as the synthetic fibers, high melting point fibers and binder fibers in a weight ratio of 20-70:80-30. 2. The chemical solution-impregnated substrate according to 1, wherein the natural fiber has an overall freeness of 500 ml or more. 3. Grammage: 120g / m 2 and the density is 0.55g / cm 3 3. The chemical solution-impregnated substrate according to 1. or 2, characterized in that: 4. The chemical solution-impregnated substrate according to any one of 1. to 3., wherein the high melting point fiber is mainly made of polyester fiber. 5. The chemical solution-impregnated substrate according to any one of 1. to 4., wherein the binder fibers are core-sheath polyester fibers. 6. The substrate for chemical liquid impregnation according to any one of 1. to 5., characterized in that the tensile strength measured according to JIS P8113 is 2.0 kN / m or more, and the wet tensile strength measured according to JIS P8135 is 0.4 kN / m or more. Effect of the Invention
[0007] According to the present invention, it is possible to provide a substrate for chemical liquid impregnation, which has a high chemical liquid impregnation rate and is less likely to break during the chemical liquid impregnation step. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Chemical impregnation substrate The substrate for chemical solution impregnation of the present invention is a single-ply or multi-ply paper, and has at least one paper layer made from a slurry of natural fibers, synthetic high-melting-point fibers, and binder fibers mixed in a predetermined ratio as a papermaking raw material, and can be manufactured using a papermaking machine used for known papermaking applications.
[0009] (Natural Fibers) The natural fibers include wood pulps such as coniferous pulp and hardwood pulp, bast fibers such as flax, ramie, jute, kenaf, hemp, paper mulberry, and mitsumata, hard fibers such as bagasse, bamboo, and esparto, seed hair fibers such as cotton pulp, and non-wood pulps such as leaf sheath and leaf fibers such as abaca and sisal, and one or more of these can be used. Note that the hemp pulp that can be used is flax, ramie, jute, kenaf, hemp, abaca, sisal, etc. As the natural fibers used in the present invention, hemp pulp or softwood pulp, which has relatively long fiber length, is preferably used to ensure the wet strength and air permeability required for the base material, and these may be used in combination. When using natural fibers such as hemp pulp and softwood pulp, each natural fiber may be beaten separately and then mixed, or multiple natural fibers may be mixed and beaten (called mixed beating) before use.
[0010] The total freeness of the natural fiber is preferably 500ml or more. The total freeness is the Canadian standard freeness measured according to JIS P8121-2:2012, and when two or more kinds of natural fibers are mixed, it is the freeness after mixing the natural fibers in a predetermined ratio. A base material made from natural fibers beaten to a total freeness of less than 500ml may not achieve the target chemical impregnation speed because it is difficult to reduce the density and the voids in the base material become small. The total freeness is preferably 550ml or more, and more preferably 600ml or more. In addition, if the total freeness exceeds 800ml, the tensile strength decreases, so that breakage may occur during the papermaking process, or even if papermaking is possible, the wet strength may decrease and the base material may break during the chemical impregnation process.
[0011] (Synthetic Fibers) The synthetic fibers include high melting point fibers and binder fibers. By blending high melting point fibers, binder fibers, and natural fibers, the high melting point fibers do not melt or soften under the heat and pressure treatment conditions during papermaking, and the base material obtained by papermaking can achieve the desired density without losing strength. This makes it possible to prevent deterioration of liquid absorption.
[0012] High melting point fiber High melting point fibers are fibers with a melting point of 150°C or higher, and are able to maintain their fibrous shape without melting during the drying process in papermaking. The type of high melting point fiber is not particularly limited, and one or more of the following fibers may be arbitrarily blended: mainly polyester fiber (PET fiber), mainly polypropylene fiber (PP fiber), polyphenylene sulfide fiber (PPS fiber), and rayon fiber. Taking into consideration the selectability of fiber length and fineness, and machine soiling during the papermaking process, mainly polyester fiber is preferred. The melting point of the high melting point fiber is preferably 160° C. or higher, more preferably 180° C. or higher, and even more preferably 200° C. or higher.
[0013] Binder fiber When the base material is made into paper, the binder fiber melts due to the heat and pressure applied in the dryer part, forming bonds between the papermaking fibers. Therefore, the strength of the base material can be maintained even when natural fibers with a low degree of beating or high melting point fibers that do not form bonds due to melting are used to increase liquid absorption. As the binder fiber, composite fibers such as core-sheath type, eccentric type, side-by-side type, or single component type can be used, but the use of core-sheath type composite fibers is preferred. Examples of such core-sheath type composite fibers include combinations of polyester resin-polyester copolymer resin, polyester resin-polyethylene resin, polyester resin-ethylene-vinyl alcohol copolymer resin, polypropylene resin-polyester copolymer resin, polypropylene resin-polyethylene resin, polypropylene resin-ethylene-vinyl alcohol copolymer resin, polypropylene resin-ethylene-vinyl acetate copolymer resin, polypropylene resin-polyethylene-propylene copolymer resin, etc. as the core-sheath component, but the above-mentioned examples are not limited to the above examples, and any core-sheath type composite binder fiber can be used as long as the resin used in the sheath has a lower melting point or a lower crystallinity than the resin used in the core and is fused by heat and / or pressure.
[0014] The amount of synthetic fiber to be blended with respect to the total fibers for papermaking is 20% by weight or more and 80% by weight or less. If the amount of synthetic fiber blended is less than 20% by weight, it may be difficult to balance the desired strength and liquid absorption regardless of the amount of high melting point fiber blended, and if the amount of synthetic fiber blended is more than 80% by weight, if the amount of high melting point fiber blended is high, the fibers may fall off the paper base sheet during papermaking, causing machine stains and other problems that may worsen operability, and if the amount of high melting point fiber blended is low, the amount of binder fiber blended is high, causing the paper base to stick to the dryer roll during papermaking, resulting in breakage, and other problems that may worsen operability.
[0015] The paper contains synthetic high melting point fibers and binder fibers in a weight ratio of 20-70:80-30. If the amount of high melting point fibers is less than 20% by weight, the binder fibers will be excessively heat fused, strengthening the bond points between the fibers while filling the gaps in the paper base material, which may result in poor liquid absorption. If the amount of high melting point fibers exceeds 70% by weight, the binder fibers will form fewer bond points between the natural fibers and high melting point fibers, reducing the surface strength of the paper base material, which may result in significant machine stains (especially on the dryer roll) due to the fibers (especially the high melting point fibers) falling off.
[0016] The paper base material of the present invention may be a single-ply paper or a multi-ply paper. In the case of a multi-ply paper, at least one paper layer contains natural fibers and synthetic fibers as papermaking fibers, and the synthetic fibers are contained in an amount of 20% by weight or more and 80% by weight or less relative to the papermaking fibers, and the synthetic fibers contain high melting point fibers and binder fibers in a weight ratio of 20-70:80-30. In the case of a multi-ply paper, the paper materials constituting each paper layer may be the same or different, but it is preferable that all paper layers satisfy the above-mentioned specific composition.
[0017] The basis weight of the base material is 120 g / m 2 The basis weight is preferably 120 g / m or more. 2 If it is less than this, the wet tensile strength may decrease, causing breakage during the liquid absorption process, or the desired amount of liquid absorption may not be achieved. 2 More than 180g / m is preferable. 2 At higher basis weights, the volatility of the absorbed chemical solution may deteriorate, and the effect of chemical solution volatilization may decrease. Therefore, it is preferable to adjust the upper limit of the basis weight as appropriate, taking into account costs, the chemical solution to be used, and the target usage period (volatility). The density of the substrate is 0.55 g / cm 3 A basis weight of 0.55 g / cm is preferred. 3 If it exceeds this value, the voids will be small and the amount of chemical solution absorbed may be insufficient. In addition, the density of the base material should be 0.28 g / cm3 from the viewpoint of wet tensile strength. 3 The above is preferred.
[0018] The strength of the paper base material is preferably 2.0 kN / m or more, more preferably 2.5 kN / m or more, in terms of dry tensile strength in the machine direction measured in accordance with JIS P8113. If the dry tensile strength is less than 2.0 kN / m, paper breaks may occur during the papermaking process. The strength of the paper base material is preferably 0.4 kN / m or more, more preferably 0.5 kN / m or more, in terms of wet tensile strength measured according to JIS P8135. If the wet tensile strength is less than 0.4 kN / m, the paper may break during the chemical impregnation process, making it impossible to impregnate the paper with the chemicals, and it may be necessary to use a special method, such as impregnation with a dispensing device.
[0019] (Manufacturing method) The chemical solution-impregnated substrate of the present invention can be manufactured by a method used in known papermaking applications. Specifically, it can be manufactured by using a fourdrinier paper machine, a cylinder paper machine, a short wire paper machine, a twin-wire paper machine, an on-top hybrid paper machine, a gap former machine, or the like, or a multi-layer paper machine that combines these. Additives can also be added as necessary. For example, fillers, pigments, sizing agents, coagulants, fluorescent whitening agents, aluminum sulfate, retention aids, drainage aids, dry strength agents, wet strength agents, coloring dyes, coloring pigments, water resistance agents, etc. can be used alone or in combination. These additives are preferably added internally, but can also be added (externally) by impregnation processing using a mangle, size press, etc., or surface coating using a gate roll coater, blade coater, bar coater, gravure coater, die coater, curtain coater, spray coater, etc. EXAMPLES
[0020] Example 1 A papermaking stock was prepared by mixing and stirring 28% by weight of NBKP (NBKP1) with a Canadian standard freeness (CSF) of 653 ml, 38.7% by weight of mercerized NBKP (NBKP2) with a Canadian standard freeness (CSF) of 760 ml, 20% by weight of high melting point fiber (main PET fiber, 3.3 dtex x 5 mm, melting point 260°C; manufactured by Teijin Limited), and 13.3% by weight of binder fiber (core-sheath PET binder fiber, 2.2 dtex x 5 mm, melting point 110°C; manufactured by Teijin Limited). Using this papermaking stock, a target basis weight of 150 g / m was achieved. 2 The wet paper was dried at 120° C. for 2 minutes to obtain a substrate.
[0021] Example 2 The papermaking raw materials were prepared by mixing and stirring 30.1 wt% NBKP1, 41.6 wt% NBKP2, 15.0 wt% high melting point fiber, and 13.3 wt% binder fiber, and papermaking was performed in the same manner as in Example 1 to obtain a base material. Example 3 The natural fiber composition was the same as in Example 1, and the high melting point fiber and binder fiber were mixed and stirred to obtain 13.3% by weight and 20.0% by weight, respectively, to prepare a papermaking raw material. The base material was then made in the same manner as in Example 1 to obtain a base material.
[0022] Example 4 The natural fiber composition was the same as in Example 2, and the high melting point fiber and binder fiber were mixed and stirred to give a content of 15.0% by weight and 13.3% by weight, respectively, to prepare a papermaking raw material. The paper was made in the same manner as in Example 1 to obtain a base material. Example 5 The raw materials for papermaking were prepared by mixing and stirring 30.5% by weight of NBKP1, 41.2% by weight of LBKP with Canadian Standard Freeness (CSF) of 500 ml, 12.0% by weight of high melting point fiber, and 13.3% by weight of binder fiber, and papermaking was carried out in the same manner as in Example 1 to obtain a base material.
[0023] Comparative Example 1 The papermaking raw materials were prepared by mixing and stirring 31.2 wt% NBKP1, 52.8 wt% NBKP2, 8.0 wt% high melting point fiber, and 8.0 wt% binder fiber, and papermaking was performed in the same manner as in Example 1 to obtain a base material. Comparative Example 2 The natural fiber composition was the same as in Example 3, and the high melting point fiber and binder fiber were mixed and stirred at 3.3 wt % and 30.0 wt % to prepare a papermaking raw material. The paper was made in the same manner as in Example 1 to obtain a base material. Comparative Example 3 The natural fiber composition was the same as in Example 3, and the high melting point fiber and binder fiber were mixed and stirred to obtain a papermaking raw material of 25.0% by weight and 8.3% by weight, respectively. The raw material was then made into paper in the same manner as in Example 1 to obtain a base material.
[0024] Comparative Example 4 A raw material for papermaking was prepared by mixing and stirring a natural fiber composition similar to that of Example 1 with 33.3% by weight of high melting point fiber, and papermaking was carried out in the same manner as in Example 1 to obtain a base material. Comparative Example 5 The mixture was stirred so that NBKP1 was 42.0% by weight and NBKP2 was 58.0% by weight to prepare a papermaking raw material, and papermaking was carried out in the same manner as in Example 1 to obtain a base material.
[0025] (Evaluation method) (1) Overall freeness Canadian standard freeness was measured according to JIS P8121-2:2012. (2)Basic weight Measurements were performed in accordance with JIS P8124. (3) Thickness Measurements were performed in accordance with JIS P8118. (4) Density Calculated from basis weight and thickness values.
[0026] (5) Dry tensile strength Measurements were performed in accordance with JIS P8113:2006. The dry tensile strength was evaluated as "good, fair, or bad" as follows. If the evaluation was good or fair, there was no problem in practical use. "〇": 2.5kN / m or more "△": 2.0kN / m or more and less than 2.5kN / m "×": Less than 2.0kN / m (6) Wet tensile strength Measurements were performed in accordance with JIS P8135:1998. If the wet tensile strength value falls below 0.4 kN / m, paper breakage may occur during the impregnation process. Therefore, if the value was equal to or greater than this value, it was evaluated as "Good", and if it was less than this value, it was evaluated as "Poor".
[0027] (7)Liquid absorption The measurement sample was conditioned for 24 hours in an atmosphere of 23°C and 50% RH, and a test piece (5cm x 10cm) was prepared from this sample. 40μl of the pyrethroid compound profluthrin (trade name: Fairtail (viscosity 14.1mPa·s) / manufactured by Sumitomo Chemical Co., Ltd.) was dropped onto the measurement surface of the test piece using a microsyringe, and the time until the drug penetrated the sample (liquid absorption time) was measured using a dynamic contact angle absorption tester (FIBRO 1100 DAT MKII: manufactured by FIBRO System AB). The liquid absorption was evaluated based on this liquid absorption time as follows, with a "good" or "bad" rating. "〇": Less than 12 seconds "×": 12 seconds or more
[0028] [Table 1]
[0029] ·result The chemical solution-impregnated substrates obtained in Examples 1 to 5 were less susceptible to breakage during production and had excellent liquid absorbency. The chemical solution-impregnated substrate obtained in Comparative Example 1 had a small amount of synthetic fiber blended therein, and was inferior in strength and liquid absorbency. The chemical solution-impregnated substrates obtained in Comparative Examples 2 to 4 had a ratio of high melting point fiber to binder fiber outside the range of the present invention. When the amount of high melting point fiber was too small, the liquid absorbency was poor, and when the amount of binder fiber was too small, the strength was poor. The chemical solution-impregnated substrate obtained in Comparative Example 5 was made only of natural fibers, and therefore had poor strength when wet and also poor liquid absorbency.
Claims
1. It is a single-ply or multi-ply paper, Papermaking fibers include natural and synthetic fibers, The synthetic fiber is contained in an amount of 20% by weight or more and 80% by weight or less based on the total fiber for papermaking, A chemical solution-impregnated substrate comprising a paper layer containing, as the synthetic fibers, high melting point fibers and binder fibers in a weight ratio of 20-70:80-30.
2. 2. The chemical solution-impregnated substrate according to claim 1, wherein the natural fiber has an overall freeness of 500 ml or more.
3. Basis weight: 120 g / m 2 or more, and the density is 0.55 g / cm 3 3. The chemical solution-impregnated substrate according to claim 1, wherein the chemical solution-impregnated substrate is one of the following:
4. 3. The chemical solution-impregnated substrate according to claim 1, wherein the high melting point fiber is mainly composed of polyester fiber.
5. 3. The chemical solution-impregnated substrate according to claim 1, wherein the binder fiber is a core-sheath polyester fiber.
6. 3. The chemical solution-impregnated substrate according to claim 1, wherein the tensile strength measured according to JIS P8113 is 2.0 kN / m or more, and the wet tensile strength measured according to JIS P8135 is 0.4 kN / m or more.
Citation Information
Patent Citations
Chemical-impregnation base material
JP2015193954A
Chemical liquid-impregnated substrate and production method thereof
JP2018168514A
Cited By
Electrolyte detection unit and automatic analysis device
CN122524902A